Implications of "Volatility in Quarterly Accounting Data": A Comment. - Hassler, Eugene C.; Buckmaster, Dale (The Accounting Review, 1975)
Presents a commentary on the data reported by Kiger in a study of interim report volatility. Implications overlooked in the study; Sources of volatility contained in interim reports; Why the conclusion of the study is misleading.